Hybrid PV/fuel cell based system using integrated SEPIC-Cuk converter with crow search optimized PI controller - Sankar, Yannam Ravi; Sekhar, Koritala Chandra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The study investigates a micro grid incorporating photovoltaic (PV), fuel cell and battery systems with an optimized proportional integral (PI) controller. A PV system serves as the primary green energy source, while a fuel cell acts as a supplementary source to compensate for power fluctuations. A single ended primary inductance converter (SEPIC) integrated Cuk converter boosts PV system's DC output voltage, controlled by a crow search-optimized PI (CS-PI) controller. A PI controller controls the fuel cell's minimum DC output voltage, which is raised by a boost converter to produce a controlled output. The proposed converter demonstrates robust performance across varying operational conditions with a reduced settling time of 0.9 s and an efficiency of 96.2%. A bidirectional converter links the battery to the grid, facilitating energy transfer in both directions and accommodating boost and buck operating characteristics thereby maintaining a state-of-charge (SOC) of 60%. This study employs MATLAB to establish effective PV-fuel storage control approaches, optimize energy extraction, and ensure steady power for a grid-connected system.